Review of nutritional value and putative health-effects of quince (Cydonia oblonga Mill.) fruit - Hegedűs, A.; Papp, N.; Stefanovits-Bányai, É. (International Journal of Horticultural Science, 2013)
Quince (Cydonia oblonga Mill.) has been long regarded to be a health-promoting fruit. Although it is mainly consumed in processed form, its relatively heat-stable polyphenolics were confirmed to be responsible for most of the beneficial effects. This review aims to show basic nutritional information on quince fruit such as carbohydrate, fibre, pectin and mineral element contents. In addition, vitamin and polyphenolic contents and composition as well as the physiological effects of quince consumption were also surveyed. Information on presumable protective effects against several diseases including infl ammation, atopic dermatitis, ulcers and cancer is summarized. Potential antibacterial effects of quince polyphenolics were also considered. Polyphenolics are supposed to be responsible for the major part of benefi cial health-effects, and phenolic compounds predominantly accumulate in peel. There exists a considerable extent of genetic variation in phytochemical composition among cultivars, which might be exploited in designing future breeding programs for quince improvement and opening new ways for health-related uses.